Indo-Pakistan relations: Problems and prospects for a sustained rapprochement? - Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2004)
The first meeting between India's new prime minister, Manmohan Singh, and Pakistan's president, Pervez Musharraf, on the periphery of the United Nations' General Assembly on September 24, 2004, served to foster the rapprochement between both countries that started in April 2003. Although no spectacular initiatives were announced, the conciliatory tone of the two leaders' speeches before the General Assembly and the joint statement released after their talks underscored the will on both sides to carry on with the cooperation that has been set in motion. The new dialog offers the possibility of expanding economic and social relations, something that may in turn help moderate the Kashmir conflict, which has strained bilateral relations for 57 years. Both sides have developed a new flexibility in the question of Kashmir, even if a quick solution is not on the horizon. The success of this rapprochement will depend on the Pakistani government's ability to implement this change in foreign policy in the face of intense domestic opposition. (SWP Comments / SWP)
Keywords: 320